Treatment to reduce vascular calcification in hemodialysis patients using vitamin K (Trevasc-HDK): A study protocol for a randomized controlled trial. Issue 36 (4th September 2020) - Haroon, Sabrina-Wong-Peixin; Tai, Bee-Choo; Ling, Lieng-Hsi; Teo, Lynette; Davenport, Andrew; Schurgers, Leon; Teo, Boon-Wee; Khatri, Priyanka; Ong, Ching-Ching; Low, Sanmay; Yeo, Xi-Er; Tan, Jia-Neng; et al.
Abstract: Introduction: End stage renal failure patients on hemodialysis have significant vascular calcification This is postulated to be related to sub-clinical vitamin K deficiency, which is prevalent in hemodialysis patients. Vitamin K deficiency result in the failure of the matrix GLA protein (MGP) to undergo carboxylation. MGP is a natural local inhibitor of vascular calcification and the lack of functional carboxylated MGP may contribute to increase vascular calcification. Vitamin K supplement should therefore correct this anomaly and decrease the rate or severity of vascular calcification in this population of patients on long-term maintenance hemodialysis. Our study seeks to evaluate the prevalence and the progression of vascular calcification in a cohort of maintenance hemodialysis patients. It will also evaluate the efficacy of vitamin K supplementation in reducing the progression of vascular calcification in this group of patients. Methods: This will be a single-center randomized, prospective and open-label interventional clinical trial of end stage renal failure patients on hemodialysis. We aim to recruit 200 patients. Eligible patients will be randomized to either the standard care arm or active treatment arm. Active treatment arm patients will receive standard care plus supplementation with oral vitamin K2 isoform 360 mcg 3 times weekly for a total duration of 18 months. Primary outcome measured will be absolute difference in coronary artery calcification score at 18-month between control and intervention arms. Secondary outcomes will be to compare absolute difference in aortic valve calcification, percentage of patients with regression of coronary artery calcification of at least 10%, absolute difference in aortic and systemic arterial stiffness, mortality from any cause and major adverse cardiovascular over the same period. Discussion: Evidence of successful regression or retardation of vascular calcification will support the conduct of larger and longer-term trials aimed at reducing cardiovascular disease mortality and major adverse cardiovascular events in this high-risk population using a safe and inexpensive strategy Trial registration: ClinicalTrials.gov NCT02870829. Registered on 17 August 2016 – Retrospectively registered, https://clinicaltrials.gov/ct2/show/NCT02870829 National University Hospital's Institutional Review Board (2015/01000)